Physiological Processes of Pomegranate Seedlings Grown in Vitro at the Stages of Growth and Development - Ergasheva F.S. (Zien Journals, 2022)
Murkute et al. in the direction of creating varieties of pomegranate (Punica granatum L.) in various climatic zones and zones using biotechnological methods, including seedlings free from pathogens in vitro. (2004), Singh and Khawale (2006), Chaugule et al. (2007), Sameer et al. (2009), Singh et al. (2001) conducted a study. Boboev’s studies reflected data on the dynamics of changes in some physiological parameters during the growing season and phases of pomegranate development in Central Asia. However, on the scale of our republic, almost no scientific research has been carried out in the direction of creating pomegranate varieties that are resistant to local climatic and soil conditions, and this situation determines the relevance of theoretical and practical research in this direction
Keywords: determines; conditions; soil; creating